Figurative Speech In Calum Scott's Song “You Are The Reason” - Poluan, Feibi; Liando, Nihta V. F; Mamentu, Agustine C. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
Figure of speech is an expression used for literacy needs both verbally and in writing. This study aims to identify the types of figurative speech and analyze the meaning of figurative speech found in the song lyric "You Are The Reason" by Calum Scott. This research uses descriptive-qualitative research approach. The research data are taken from Calum Scott's song You Are The Reason. The analysis used Kennedy’s figurative speech theory. From the analysis of the song lyrics, the researcher identified 5 types of figurative speech with total of 8 data and meaning. The types of figurative speech are metaphor 2 data, similes 2 data, personification 1 data, hyperbole 1 data, and symbolism 2 data. The most dominant figurative speech found in this study are metaphor, similes, and symbolism. In conclusion, Calum Scott’s "You Are the Reason" stands out for its effective use of figurative speech to convey deep emotional experiences. By applying Kennedy’s figurative speech theory, we could learn how Scott’s song transforms into a powerful narrative that deeply resonates with listeners, illustrating the enduring and universal nature of love.